Thermal storage subcooling for CO2 booster refrigeration systems. (28th May 2019) - Bush, John; Aute, Vikrant; Radermacher, Reinhard
Abstract : Transcritical CO2 supermarket refrigeration equipment is becoming more common as a near-zero global warming potential solution. Much attention is being given to improvements in efficiency for these systems, especially in transcritical operation to counteract reduced efficiency during hot outdoor temperatures. One approach to improving cycle efficiency is through the use of dedicated mechanical subcooling. This article examines further enhancement to the subcooler for the booster cycle by adding the use of thermal storage. By integrating a thermal energy storage system into the subcooling loop, the efficiency enhancements of dedicated subcooling may be maintained, while shifting power consumption to off-peak hours, significantly improving efficiency, and reducing power during hours with hot outdoor temperatures. Transient modeling was used to simulate a supermarket system with a thermal storage subcooler with different phase change material (PCM) and heat exchanger configurations. The results show a reduction of power corresponding to the power of the subcooler, with the possibility of further power reduction if the thermal storage system delivers lower leaving refrigerant temperatures. The power reduction is in the range of 8% to 16% for the duration of the storage discharge.